PENINGKATAN MUTU KINERJA KARYAWAN MELALUI MANAJEMEN ARSIP DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK DI KJKS BMT - HELMALIA HELMALIA (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2017)
The theme of the article is a business based on the principles of Islamic economics. The purpose of this research is to know the archive management in KJKS BMT. The object of research is KJKS BMT in Anduring Padang. This research raises the problem of how the archive management in KJKS BMT. The results of the study are: the low management of archive storage in KJKS BMT.